Superheated steam treatment modulates lipid–volatile metabolomics associations and improves storage stability of highland barley (Qingke) - Mengjia Li; Yang Li; Bei Fan; Jingfeng Li; Zhangjing Lu; Fengzhong Wang; Lili Wang (Food Chemistry, 2026)

Fecal pollution source tracking at a marine bathing beach: A case study of Beihai Silver Beach - Hongxia Ming; Ziqi Chen; Tingting Shi; Zhongzhi Chen; Wenjing Pan; Jiannan Lin; Jie Su; Jingfeng Fan (Regional Studies in Marine Science, 2026)

Development of an inactivated H9N2 subtype avian influenza serological DIVA vaccine using the chimeric A/B NA epitope approach - Jingfeng Zhang; Zhiyu Fan; Qunxing Pan; Fei Yu; Huawei Sun; Minhua Sun; Jinping Fu; Jiasheng Song (Veterinary Microbiology, 2026)

The trend and interannual variability in the global terrestrial evapotranspiration are respectively dominated by humid regions and drylands - Huiling Chen; Kun Zhang; Gaofeng Zhu; Lei Fan; Xin Li; Yunquan Wang; Xufeng Wang; Shasha Shang; Jia Jia; Yongtai Zhu; Jingfeng Xiao (Journal of Hydrology, 2026)

Experimental study on punching shear performance of embedded special-shaped CFST column base - Yong Liu; Zhuofei Li; Jingfeng Wang; Lanhui Guo; Fan Ye; Shasha Tan; Beibei Li (Engineering Structures, 2026)

Editor's note to “The Grain-for-Green project offsets warming-induced soil organic carbon loss and increases soil carbon stock in Chinese Loess Plateau” [Sci. Total Environ. 837 (2022), 155469] - Huiwen Li; Yiping Wu; Shuguang Liu; Wenzhi Zhao; Jingfeng Xiao; Leigh A. Winowiecki; Xiaowei Yin; Fan Wang; Bellie Sivakumar; Yue Cao; Pengcheng Sun (Science of The Total Environment, 2026)

Preparation and digestive behavior of ferulic acid-bacterial cellulose/arabinoxylan complex with strong antioxidant activity - Xueqing Wang; Giorgia Purcaro; Yang Li; Jingjing Yang; Lang Jia; Jingfeng Li; Bei Fan; Yatao Huang; Fengzhong Wang; Lili Wang (Carbohydrate Polymers, 2026)

Environmental DNA reveals shift in phytoplankton community driven by sewage-derived eutrophication in coastal waters - Jie Su; Xuexin Wu; Tingting Shi; Shanshan Dong; Daoyang Shi; Hanjun Chen; Hongxia Ming; Jingfeng Fan (Marine Environmental Research, 2026)

Ligation-mediated circuit-driven cascade amplification with high utilization rate of template for lncRNA MALAT1 detection in cancer mice tissues - Yuyan Huang; Fan Huang; Qianqian Du; Rui Yu; Jingfeng Lan; Junwei Luo; Hongli Chen; Huige Zhang (Analytica Chimica Acta, 2026)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Estimating carbon fluxes over North America using a physics-constrained deep learning model - Bin Fan; Hankui K. Zhang; Zhongbin B. Li; Jingfeng Xiao; Xianghong Che; Zhihua Liu; Gustau Camps-Valls; Jing M. Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Assessment of spatial and temporal variability in fecal contamination patterns within urbanized bay shellfish growing area utilizing community-based microbial source tracking approaches - Jiannan Lin; Hongxia Ming; Dongwei Li; Jiajie Li; Zhongzhi Chen; Ziqi Chen; Tingting Shi; Jie Su; Jingfeng Fan (Environmental Monitoring and Assessment, 2025)

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Pilot-scale application of sludge fermentation-driven nitrogen removal process with rapid in-situ enrichment of anammox bacteria for sustainable treatment of municipal wastewater and excess sludge - Shiwei Hao; Li Zhang; Jingfeng Gao; Xuepeng Fan; Tingjun Dong; Jiachun Yang; Shuang Lan; Yongzhen Peng (Chemical Engineering Journal, 2025)

Microbial degradation of DOC released by the mixed culture of Crassostrea gigas and Undaria pinnatifida - Tian Hu; Jie Su; Kuishuang Shao; Shanshan Dong; Yuyang Xie; Yawen Wei; Hongxia Ming; Tingting Shi; Ge Guo; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Nitrogen are the main factors driving the structure and function of the marine archaeal community in Yongle Blue Hole, Sansha - Wenjing Wang; Hongxia Ming; Dongwei Li; Yuan Jin; Yuyang Xie; Jingfeng Fan (Regional Studies in Marine Science, 2024)

Spinach leaf disease identification based on deep learning techniques - Laixiang Xu; Jingfeng Su; Bei Li; Yongfeng Fan; Junmin Zhao (Plant Biotechnology Reports, 2024)

Satellite-based monitoring of China's above-ground biomass carbon sink from 2015 to 2021 - Hongqian Fang; Lei Fan; Philippe Ciais; Jingfeng Xiao; Rasmus Fensholt; Jingming Chen; Frédéric Frappart; Weimin Ju; Shuli Niu; Xiangming Xiao; Wenping Yuan; Jiangzhou Xia; et al. (Agricultural and Forest Meteorology, 2024)

Promoting the denitrification process by heavy metals in Liaohe Estuary sediment - Ming Hongxia; Zan Shuaijun; Liu Jiwen; Su Jie; Ren Kaijia; Lin Jiannan; Chen Quanrui; Shi Yinyin; Shi Tingting; Fan Jingfeng (Marine Pollution Bulletin, 2024)

Spatial heterogeneity plays a vital role in shaping the structure and function of estuarine carbon-fixing bacterial communities - Jianrong Xu; Hongxia Ming; Kaijia Ren; Dongwei Li; Huiling Huang; Jiajie Li; Kuishuang Shao; Hongjun Li; Jingfeng Fan (Marine Environmental Research, 2024)

Spatial distribution characteristics and interaction effects of DOM and microbial communities in kelp cultivation areas - Huiling Huang; Shuaijun Zan; Kuishuang Shao; Hanjun Chen; Jingfeng Fan (Science of The Total Environment, 2024)

Long-term response of the microbial community to the degradation of DOC released from Undaria pinnatifida - Yuyang Xie; Jie Su; Kuishuang Shao; Tian Hu; Hongxia Ming; Tingting Shi; Wenjing Wang; Jingfeng Fan (Marine Environmental Research, 2024)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Marine toxin domoic acid alters protistan community structure and assembly process in sediments - Zelong Li; Jing Wang; Jingfeng Fan; Hao Yue; Xiuhong Zhang (Marine Environmental Research, 2023)

A comprehensive review of calcium and ferrous ions chelating peptides: Preparation, structure and transport pathways - Qiaoji Tian; Yan Fan; Li Hao; Jie Wang; Chensi Xia; Jingfeng Wang; Hu Hou (Critical Reviews in Food Science and Nutrition, 2023)

A new pathway for anaerobic biotransformation of marine toxin domoic acid - Miaomiao Du; Yuan Jin; Jingfeng Fan; Shuaijun Zan; Chen Gu; Jing Wang (Environmental Science and Pollution Research, 2023)

Prevalence, antibiotic and heavy metal resistance of Vibrio spp. isolated from the clam Meretrix meretrix at different ages in Geligang, Liaohe estuary in China - Jie Su; Yingxue Zhang; Tian Hu; Hongxia Ming; Yuyang Xie; Yuan Jin; Tingting Shi; Jingfeng Fan (Frontiers in Marine Science, 2022)
Vibrio as one of the main pathogens of shellfish diseases can cause serious human seafoodborne gastroenteritis and even death. In this study, we analyzed the bacterial communities from the clam, and compared the resistance phenotypes and genotypes of Vibrio spp. from Meretrix meretrix at different growth stages. High-throughput sequencing analysis revealed the predominance of Proteobacteria (50%) in the bacterial community and Vibrio was one of the dominant genera in the clam hepatopancreas in the summer. Vibrio abundance in Meretrix meretrix positively correlated with the water temperature (p<0.05). A total of 73 Vibrio isolates from Meretrix meretrix were classified into 19 species and the dominant strains included V. mediterranei (19%) and V. harveyi (11%), V. algolyticus (10%), and V. parahaemolyticus (8%). The species and abundance of Vibrio spp. were the highest in the 3-year-old of Meretrix meretrix compared with clams of other ages in the summer. Among the 73 isolates, 68 Vibrio strains were resistant to other 15 antibiotics except for sulfamethoxazole-trimethoprim with 57 resistant phenotypes. The most prevalent resistance was toward clindamycin (76%), followed by amikacin (63%), ampicillin (62%), rifampicin (62%), vancomycin (57%), and amoxicillin (50%). The ARI values of Vibrio spp. in different ages ranged from 0.13 to 0.18, and ARI values of 3-year-old (ARI=0.18) clams are higher than that of other ages clam. Approximately 72% of the resistant isolates showed multidrug-resistant phenotypes with maximum resistance to 15 antibiotics. Tolerance to heavy metals including Cd, Zn, and Cu was detected in the majority of antibiotic resistant isolates. In addition to the co-resistance to the same class of antibiotics, resistance to cephalosporin (CFP, CEP, CZ) were significantly correlated with penicillins (AMP, AMC) ( p < 0.01), tetracycline ( p < 0.001), sulfanilamide (SXT) ( p < 0.01) and quinolone (CIP) ( p < 0.01). The heavy metal resistance genes copB and nccA were significantly correlated with the clindamycin resistance phenotype ( p <0.01). This study revealed that the habitat of Meretrix meretrix is in low exposure to antibiotics, and a link between heavy metal resistance genes and antibiotic resistance.

Cyclohexanecarboxylic acid degradation with simultaneous nitrate removal by Marinobacter sp. SJ18 - Shuaijun Zan; Jing Wang; Jingfeng Fan; Yuan Jin; Zelong Li; Miaomiao Du (Environmental Science and Pollution Research, 2022)

16S Next-generation sequencing and quantitative PCR reveal the distribution of potential pathogens in the Liaohe Estuary - Huiling Huang; Shuaijun Zan; Hongxia Ming; Mengfei Li; Jianrong Xu; Yuyang Xie; Wenjing Wang; Jingfeng Fan (Frontiers in Marine Science, 2022)
The existence of potentially pathogenic bacteria seriously threatens aquatic animals and human health. Estuaries are closely related to human activities, and the detection of pathogens is important for aquaculture and public health. However, monitoring only indicator microorganisms and pathogens is not enough to accurately and comprehensively estimate water pollution. Here, the diversity of potentially pathogenic bacteria in water samples from the Liaohe estuary was profiled using 16S next-generation sequencing (16S NGS) and quantitative polymerase chain reaction (qPCR) analysis. The results showed that the dominant genera of environmental pathogens were Pseudomonas , Vibrio , Mycobacterium , Acinetobacter , Exiguobacterium , Sphingomonas , and Legionella , and the abundance of enteric pathogens was significantly less than the environmental pathogens, mainly, Citrobacter , Enterococcus , Escherichia-Shigella , Enterobacter , Bacteroides . The qPCR results showed that the 16S rRNA genes of Vibrio were the most abundant, with concentrations between 7.06 and 9.48 lg copies/L, followed by oaa gene, fliC gene, trh gene, and uidA gene, and the temperature and salinity were the main factors affecting its abundance. Variance partitioning analysis (VPA) analysis of spatial factors on the potential pathogen’s distribution (19.6% vs 5.3%) was greater than environmental factors. In addition, the co-occurrence analysis of potential pathogens in the estuary revealed significant co-occurrence among the opportunistic pathogens Testosteronemonas , Brevimonas vesicularis , and Pseudomonas putida . Our findings provide an essential reference for monitoring and occurrence of potentially pathogenic bacteria in estuaries.

Comprehensive evaluation and analysis of the salinity stress response mechanisms based on transcriptome and metabolome of Staphylococcus aureus - Ying Feng; Dizhou Gu; Ziyan Wang; Chenyang Lu; Jingfeng Fan; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2022)

Spatial distribution characteristics of bacterial community structure and gene abundance in sediments of the Bohai Sea - Quanrui Chen; Jingfeng Fan; Jie Su; Hongxia Ming; Zhihao Sun; Mengfei Li; Xiaohui Zhao; Yantao Wang; Yingxue Zhang; Huizhen Zhang; Yuan Jin; Xiaowan Ma; et al. (Acta Oceanologica Sinica, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Preparation, Gel Electrophoresis Analysis, and Nutritional Evaluation of a Functional Krill Protein Concentrate with Low Fluoride Level from Antarctic krill ( Euphausia superba ) - Li’ang Yin; Xiaoming Jiang; Yan Fan; Jingfeng Wang; Changhu Xue; Yong Xue (Journal of Aquatic Food Product Technology, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)

Spatial Abundance, Diversity, and Activity of Ammonia-Oxidizing Bacteria in Coastal Sediments of the Liaohe Estuary - Yongkai Chang; Jingfeng Fan; Jie Su; Hongxia Ming; Wen Zhao; Yan Shi; Fengyun Ji; Limei Guo; Shuaijun Zan; Bochao Li; Hao Guo; Daoming Guan (Current Microbiology, 2017)

Diversity and structure of bacterial communities in Fildes Peninsula, King George Island - Jingfeng Fan; Lili Li; Junli Han; Hongxia Ming; Jiangyu Li; Guangshui Na; Jiaying Chen (Polar Biology, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)